Parental attachment, self‐control, and depressive symptoms in Chinese and Italian adolescents: Test of a mediation model. (28th June 2015) - Li, Jian‐Bin; Delvecchio, Elisa; Lis, Adriana; Nie, Yan‐Gang; Di Riso, Daniela
ABSTRACT: The current study investigated the relationship between parental attachment and depressive symptoms as well as the mediating effect of self‐control in two different cultures. Samples were 1305 Chinese and 1327 Italian adolescents. They completed the Inventory of Parental and Peer Attachment, the Self‐Restraint Subscale of the Adolescents' Self‐Consciousness Scale, and the Children's Depression Inventory that assessed parental attachment, self‐control, and depressive symptoms, respectively. Results showed that: (1) Few cultural differences in depressive symptom were observed. (2) Parental attachment and self‐control were negatively related to depressive symptoms in both cultures. (3) Self‐control mediated the relations between parental attachment and depressive symptoms in both cultures. (4) The direct and indirect effects were invariant across cultures. In conclusion, parental attachment and self‐control are important for adolescents' depressive symptoms in Chinese and Italian adolescents.